Smoking prevalence and effects on treatment outcomes in patients with tuberculosis - Vargas, Kellyn Rocha de (2021)
OBJECTIVE: More than 20% of tuberculosis (TB) cases worldwide are attributable to smoking, and it is associated with an increased risk of latent and active TB, recurrence, and mortality. The aim of this study is to assess the smoking prevalence and the effects on treatment outcomes in TB patients. METHODS: A prospective cohort study was conducted in patients with a recent TB diagnosis. The smoking status was defined, in addition to the patients’ knowledge and attitudes toward smoking. The patients were followed up until the end of the treatment, and the treatment result was recorded. RESULTS: Ninety-two patients were included in this study. The prevalence of active smoking was 31.5%. Active smokers had less chance for cure (62.1% versus 82.5%; p=0.032) and more treatment dropout (31.0% versus 12.7%; p=0.035) than non-active smokers. Patients demonstrated positive attitudes and good knowledge about smoking. CONCLUSIONS: Active smokers had less chance for cure and more abandonment than non-active smokers. These results can be useful for the proper planning of actions that impact TB control, especially in the treatment results, such as cognitive-behavioral approaches to smoking cessation.